Pengaruh Penggunaan Instant Messaging (WhatsApp) Pada UKM di Lingkungan Apartemen Kota Jakarta Selatan - Sistarani Meutia; Umar Abdullah; Sasongko Hari Agung (BBM (Buletin Bisnis & Manajemen), 2018)
Along with the development of technology and social culture, has evolved other media whichthen grouped into mass media such as internet and mobile phone. The use of smartphones(mobile phones) in everyday activities can be utilized well as an opportunity for the perpetratorsof Small and Medium Enterprises (SMEs). One of the locations that can be used as a place ofbusiness is in an apartment environment located in South Jakarta. This research is conducted byusing qualitative descriptive method which improves data done by observation and interviewwith business owner, employee, and consumer. The marketing mix (marketing mix) consisting of7P (product, price, place, promotion, physical evidence, person, and process) is used in themarketing plan plan. The results of this study will be able to see the effect of the use of instantmessaging (WhatsApp) in Small and Medium Enterprises in the neighborhood of South JakartaMunicipality.Keywords: instant, messaging, whatsapp, apartment, marketing mix